Defining the efficient relation between different climate change policies. (30th September 2019) - Porrini, Donatella
The COP 21 conference in Paris provided for individual nationally determined contributions as necessary key conditions to face the phenomenon of climate change, originating from greenhouse gas emissions. As a matter of fact, countries all over the world are implementing, or planning to implement, different policies, ranging from command and control regulations to market-based systems (such as carbon tax or cap-and-trade systems). The question addressed in this paper is whether the link between heterogeneous policies can help to minimise the inefficiencies characterising the use of a single policy at national or regional levels. In the introduction, the traditional analysis of the choice of environmental policies is connected with the concept of 'economic global public goods'. The following part describes the different environmental policy instruments in relation to climate change. The third paragraph deals with the comparison between taxes and tradable permits as a question of 'quantity' versus 'price' control. The fourth paragraph is about the linkage between different environmental policy instruments, with a specific reference to the joint use of a cap-and-trade system with a taxation scheme. Finally, some conclusive remarks are presented in relation to the prospect of linking different policies, in the future, at a global level.